Diagnostic yield of video capsule endoscopy in obscure occult gastrointestinal bleed - Gaikwad, Nitin R.; Gupta, Sudhir J.; Sankalecha, Tushar H.; Kothari, Harit G. (International Journal of Research in Medical Sciences, 2017)
Background: Gastrointestinal blood loss is the leading cause of iron deficiency anemia in developing world. Many patients had normal findings on initial upper and lower gastrointestinal endoscopy. When such patients present with stool occult blood positivity, it’s an indication to evaluate small bowel by video capsule endoscopy for detecting possible source of bleeding. Aim was to know the diagnostic yield of video capsule endoscopy in anaemic patients with occult gastrointestinal bleed. Methods: In this retrospective study, we evaluated all the data of video capsule endoscopy which were done in patients with obscure occult gastrointestinal bleed. Results: Total sample size was 21 patients. M:F ratio was 1.6:1 Average age of patients was 51.52±6.3 years. Youngest patient was of 16 years and Oldest patient was of 78 years. Video capsule endoscopy was normal in 8/21(38.09%), and had positive findings in 13/21(61.90%). Most common finding was aphthous ulcer in jejunum and ileum in 19.04%. Followed by Telangiectasia in 14.28%, NSAID enteropathy in 4.76%, Jejunal diverticulosis in 9.52%, celiac disease, xanthelasma, enteroliths in ileum, ileal nodularity in 4.76% each. Complication occurred in one patient (4.76%) in the form of retention of the capsule, which was retrieved by double balloon Enteroscopy. Conclusions: Video capsule endoscopy has a good diagnostic yield of around 61.90% in patients with obscure occult gastrointestinal bleed. It is best performed during ongoing bleed or immediately thereafter. Careful patient selection and repeating the upper and lower GI Scopy before video capsule endoscopy can be a reliable option before video capsule endoscopy to prevent complication.